Comparative genomic and transcriptome analyses of two Pectobacterium brasiliense strains revealed distinct virulence determinants and phenotypic features - Sun, Yue; Utpal, Handique; Wu, Yajuan; Sun, Qinghua; Feng, Zhiwen; Shen, Yue; Zhang, Ruofang; Zhou, Xiaofeng; Wu, Jian (Frontiers in Microbiology, 2024)
Potato soft rot caused by Pectobacterium spp. are devastating diseases of potato which cause severe economic losses worldwide. Pectobacterium brasiliense is considered as one of the most virulent species. However, the virulence mechanisms and pathogenicity factors of this strain have not been fully elucidated. Here, through pathogenicity screening, we identified two Pectobacterium brasiliense isolates, SM and DQ, with distinct pathogenicity levels. SM exhibits higher virulence compared to DQ in inducing aerial stem rot, blackleg and tuber soft rot. Our genomic and transcriptomic analyses revealed that SM encodes strain specific genes with regard to plant cell wall degradation and express higher level of genes associated with bacterial motility and secretion system. Our plate assays verified higher pectinase, cellulase, and protease activities, as well as fast swimming and swarming motility in SM. Importantly, a unique endoglucanase S specific to SM was identified. Expression of this cellulase in DQ greatly enhances its virulence compared to wild type strain. Our study sheds light on possible determinants causing different pathogenicity of Pectobacterium brasiliense species with close evolutionary distance and provides new insight into the direction of genome evolution in response to host variation and environmental stimuli.